2013
DOI: 10.1021/ol401029k
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Vabicaserin via Oxidative Multicomponent Annulation and Asymmetric Hydrogenation of a 3,4-Substituted Quinolinium Salt

Abstract: An efficient, asymmetric synthesis of the 5-HT2C agonist vabicaserin in four chemical steps and 54% overall yield from commercially available benzodiazepine was achieved. The synthesis was highlighted by a novel oxidative, multicomponent reaction to affect the quinolinium ring assembly in one step followed by an unprecedented asymmetric hydrogenation of a 3,4-substituted quinolinium salt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…These reactions allow the generation of complex compounds from simple raw materials in one-step. Scheme 7 always portrays a multicomponent coupling process for the synthesis of vabicaserin [17][18][19][20]. The synthesis of azoindole is also a multicomponent reaction that involves simple ketones and the haloaminpyridines.…”
Section: Via Multicomponent Couplingmentioning
confidence: 99%
“…These reactions allow the generation of complex compounds from simple raw materials in one-step. Scheme 7 always portrays a multicomponent coupling process for the synthesis of vabicaserin [17][18][19][20]. The synthesis of azoindole is also a multicomponent reaction that involves simple ketones and the haloaminpyridines.…”
Section: Via Multicomponent Couplingmentioning
confidence: 99%
“…The authors also found (by measure of infrared CO stretching frequencies) dimethyl-substituted phospholes are more electron-donating than either alkyl-or aryl-substituted phosphines; in their screening efforts, increased ligand electrondonating ability had appeared to correlate with improved enantioselectivity. In 2013, Dragan, McWilliams, and Miller [41] used [Ir(cod)Cl] 2 and the chiral phosphoramidite (S)-MorPhos to enantioselectively hydrogenate the quinolinium core of a precursor to the potential anti-psychotic agent Vabicaserin (Scheme 11). Addition of P( t Bu) 3 and LiCl were found to improve catalyst activity and enantioselectivity respectively.…”
Section: Asymmetric Hydrogenationmentioning
confidence: 99%
“…Compounds containing the tetrahydrobenzodiazepine moiety find numerous applications in medicinal chemistry, for example, BMS-214662, which exhibits potent antitumor activity (Figure ). , Also tetrahydrobenzodiazepines have been used as intermediates in organic synthesis. Compounds that possess the imidazopyridine moiety display antitumor, antifungal, antibacterial, antiviral, and antiprotozoal activities, and some are currently marketed drugs such as zolpidem used for the treatment of sleep disorder (Figure ), anxyolitic drug alpidem and antiulcer drug zolimidine . Tetrahydroquinoxalines have been studied as potent cholesteryl ester transfer protein inhibitors (Figure ), anticonvulsants, potassium channel openers, and anti-HIV agents …”
Section: Introductionmentioning
confidence: 99%